Analysis of Potential Hazards and Control in PT XYZ's Production Process with the HIRADC Method - Tika Puspitasari; Ismianti Ismianti (OPSI, 2023)
In carrying out the production process, the company must pay attention to the health and safety of the workforce to support labor productivity. However, K3 at PT XYZ, especially in the production process, is still not going well according to the law, one of which is the use of PPE is considered not important by the workforce. This study aims to analyze the risks and controls in the production process. This research was conducted by identifying potential hazards by categorizing them into risk levels and determining the control of potential hazards in the production process using the HIRADC method. The results of this study indicate that there are 9 risks in the production division, with the grouping of 5 risks classified as high risk (high) which includes high risks such as bandsaw regarding sawdust, assembly, 1 moderate risk (moderate) risk, namely the raw material part, and 3 the risk is classified as low risk (low) which includes low risk such as band saw machines for chop saws. Based on the results of the risk assessment, most machines are classified as high risk, so it is necessary to improve the implementation of K3 and improve the source of danger. Of all the hazards and risks in the production division of PT XYZ, an analysis of potential hazards and their control is carried out using the HIRADC method. The recommendations given include completing PPE, carrying out engineering for example, carrying out eliminations such as using dust powder covers and using push sticks.